Pengukuran Kinerja Bank Syariah dengan Metode RGEC - Umiyati Umiyati; Queenindya Permata Faly (SEKOLAH TINGGI EKONOMI ISLAM SEBI, 2015)
This research is on purpose to discover any significant differences on Panin SyariahBank work performance before and after go public using the RGEC Method, and alsoto find out how large the difference performance of it. Data used in this research was asecondary data which took from financial report quarterly era 2013-2014 that hasbeen published. Meanwhile, that method used was a comparison method usingstatistic non parametric test equipment two related samples (wilcoxon test). The resultin this research shows that variable of capital adequacy ratio (CAR) had a significantdifference, because of having a sig. value 0,05. While other variable (l.e. NonPerforming Financing (NPF), Financing to Deposit Ratio (FDR), Return On Asset(ROA), Return On Equity (ROE), Net Interest Margin (NIM) or Net OperatingMargin (NOM), and Good Corporate Governance